Dr. Hania Ris's Contribution to Wisconsin's Contraceptive Legislation - Boese, Matt (My University, 2012)
Although a large amount of media attention is currently focused on women's reproductive health issues, most Wisconsinites are unfamiliar with their state's conservative history in the area of contraceptive accessibility. This paper focuses on Wisconsin legislation during the 1960s and 1970s that did not allow distribution of birth control to minors or the unmarried. The work of Dr. Hania Ris, which is unbeknownst to many, is the primary emphasis of my research. My thesis was formulated after searching through the copious amounts of archival materials that Ris made available in the Wisconsin Historical Society. Newspaper archives were also utilized to underscore the local and national impact of Ris and the work that is detailed in her records. Together, these materials provide a glimpse into one piece of Ris's activism and demonstrate how important she is in Wisconsin's history of birth control politics.
Keywords: Birth control; Hania Ris; Contraception; Reproductive rights